2006
DOI: 10.1089/fpd.2006.3.432
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Seeking Medical Care and Submitting a Stool Sample in Estimating the Burden of Foodborne Illness

Abstract: Laboratory-based surveillance is a foundation for public health and is essential for determining the incidence of most foodborne diseases caused by bacterial pathogens; however, reported cases represent a subset of infections in the community. To identify the factors associated with seeking medical care and submitting a stool specimen among persons with acute diarrheal illness, we used multivariate logistic regression to analyze data from two 12- month population-based telephone surveys conducted in the Foodbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
5
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 15 publications
9
106
5
1
Order By: Relevance
“…Tam et al (2003) found that individuals with lower educational levels were more likely to consult a general practitioner than more highly educated individuals. Scallan et al (2006) observed a similar trend, although the difference was not statistically significant 44 . An individual's educational level can influence one's health beliefs, perceptions of health status, and ultimate need for seeking healthcare 41;45 .…”
Section: Impact Of Socioeconomic Factorsmentioning
confidence: 71%
“…Tam et al (2003) found that individuals with lower educational levels were more likely to consult a general practitioner than more highly educated individuals. Scallan et al (2006) observed a similar trend, although the difference was not statistically significant 44 . An individual's educational level can influence one's health beliefs, perceptions of health status, and ultimate need for seeking healthcare 41;45 .…”
Section: Impact Of Socioeconomic Factorsmentioning
confidence: 71%
“…First, microbiology test results are very specific for acute enteric illness, and even with a low RI, a cluster suggestive of a true outbreak was identified of genetically related isolates (Table 5, potential outbreak B). Also, stool culture orders reflect clinician suspicion of acute illness and disproportionately represent patients with bloody diarrhea and diarrhea duration of ‡ 3 days (Scallan et al, 2006); it is unknown whether the intriguing potential outbreak identified (Table 3) reflected a true outbreak or something else, but it represents the type of event that public health officials may be interested in prospectively detecting. Finally, outpatient diagnoses contributed to the most potential outbreaks (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Case patients were recruited from notified, laboratory-confirmed cases and may not be representative of all yersiniosis cases in the population. Patients seeking medical care and triggering microbiological examination of stool samples because of a gastrointestinal illness are more likely to be young children or to suffer from a more severe or prolonged course of illness [29]. Furthermore, detailed clinical information on case patients, for example on complications such as concurrent bacteraemia in young children, is not routinely collected through the notification system [3].…”
Section: Discussionmentioning
confidence: 99%